Clinical outcomes of concurrent use of corticosteroids and immune checkpoint inhibitors in oncology - Moskalenko, Y.; Kravets, O.; Kovchun, V. (Regulatory Mechanisms in Biosystems, 2025)
Immunotherapy has transformed metastatic non-small cell lung cancer (mNSCLC) treatment. Immune checkpoint inhibitors (ICIs) enhance antitumor immunity, but systemic corticosteroids may counteract their effects. While systemic corticosteroids are known to impair ICI outcomes, the impact of inhaled corticosteroids remains unclear. This study assessed the influence of systemic corticosteroids and inhaled corticosteroids on ICI efficacy in mNSCLC patients. This single-center cohort study included 105 mNSCLC patients receiving pembrolizumab or atezolizumab (2016–2024). Patients were classified into three groups: (1) no corticosteroids, (2) systemic corticosteroids use (≥10 mg prednisolone-equivalent), and (3) inhaled corticosteroids use. Clinical outcomes included objective response rate, disease control rate, progression-free survival, and overall survival. Kaplan-Meier analysis and Cox regression evaluated corticosteroid impact. Analyses were conducted using Stata 18.0. Among the 105 patients, 38 r e ceived systemic corticosteroids (S CS) , 16 received inhaled corticosteroids (ICS) , and 51 did not receive corticosteroids. ICS use was associated with chronic obstructive pulmonary disease, while SCS use was more frequent in older patients . Patients receiving systemic corticosteroids exhibited significantly worse progression-free survival (4.1 vs. 8.6 months in the non-steroid group) and overall survival (6.9 vs. 20.1 months). Inhaled corticosteroid use did not negatively impact survival (median overall survival: 35.1 months). Multivariate analysis identified systemic corticosteroid use and cardiovascular disease as independent predictors of poor prognosis, while chronic obstructive pulmonary disease was associated with improved outcomes. Notably, long-acting sy s temic corticosteroids (dexamethasone) were linked to worse survival than intermediate-acting systemic corticosteroids (4.7 vs. 9.7 months). In conclusion, systemic corticosteroids, especially long-acting forms, significantly reduce ICI efficacy and predict worse survival in mNSCLC. Conversely, inhaled corticosteroid use does not impair treatment outcomes. Chronic obstructive pulmonary disease may be a favorable prognostic factor for immunotherapy response. These findings highlight the importance of cautious corticosteroid use in optimizing ICI therapy.